Analysis of Students' Higher Order Thinking Skills (HOTS) in PAI Learning at SMK Marhas Margahayu: Analisis Kemampuan Higher Order Thinking Skills (HOTS) Siswa Dalam Pembelajaran PAI di SMK Marhas Margahayu - Fauzi, Rai Ahmad; Ramdhani, Muhammad Ali; Hambali, Adang (CV. Media Publikasi Profesional, 2023)
This study aims to analyse students' higher order thinking skills (HOTS) in Islamic Religious Education (PAI) subjects, especially at the levels of analysis (C4), evaluation (C5), and creation (C6). This research is important considering the low achievement of Indonesian students' HOTS in the national education evaluation. The method used was descriptive quantitative, with data collection techniques through Google Form-based written tests to 18 students of class XII SMK Marhas Margahayu. The data was analysed using percentage and average score techniques to measure students' ability levels. The results showed that the majority of students were in the low to very low category, with an average score of 51.85. Only a small number of students reached the high category, indicating the potential for HOTS development through appropriate learning strategies. This finding indicates that PAI learning is still dominantly focused on memorisation and has not optimally developed critical and reflective thinking. The implication of this study is the need to improve learning and evaluation strategies in PAI to better encourage students' higher order thinking skills. In an original way, this research contributes to the development of contextualised HOTS-based evaluative instruments in PAI learning at the vocational level and offers an alternative approach in improving the quality of religious learning in vocational schools.